2021
DOI: 10.1002/ejp.1716
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐accumbal dopaminergic system modulates the restraint stress‐induced antinociceptive behaviours in persistent inflammatory pain

Abstract: Background: Stress activates several neural pathways that inhibit pain sensation. Nucleus accumbens (NAc), as an important component of the mesolimbic dopaminergic system, has a major role in pain modulation and is differentially affected by stress. Based on the nature of stressors, the direction of this effect is controversial. We previously showed that forced swim stress-induced analgesia through activation of NAc dopamine receptors. In this study, we aimed to examine the role of dopamine receptors within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Moreover, based on the duration of stressors, various responses to pain have been observed in laboratory animals, such as SIA or stress-induced hyperalgesia (SIH). For example, one-time exposure to the RS (Faramarzi et al , 2021) or the FSS (Faramarzi et al , 2016) induces analgesia, whereas repeated swim stress (Quintero et al , 2000) and chronic daily exposure to the RS (Scheich et al , 2017) appeared to produce the SIH instead of the SIA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, based on the duration of stressors, various responses to pain have been observed in laboratory animals, such as SIA or stress-induced hyperalgesia (SIH). For example, one-time exposure to the RS (Faramarzi et al , 2021) or the FSS (Faramarzi et al , 2016) induces analgesia, whereas repeated swim stress (Quintero et al , 2000) and chronic daily exposure to the RS (Scheich et al , 2017) appeared to produce the SIH instead of the SIA.…”
Section: Discussionmentioning
confidence: 99%
“…Both rewarding and aversive stimuli, such as stressors, potently activate specific dopaminergic neurons in the VTA (Holly and Miczek, 2016). Previously, we have demonstrated that dopamine receptors within the NAc contribute to both forced swim stress (FSS) and restraint stress (RS)induced analgesia during persistent inflammatory pain (Faramarzi et al, 2016(Faramarzi et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, it is well-known that DA receptors are widely expressed in the different regions of the nervous system, playing their vital roles in neuromodulation (Klein et al ., 2019). In this regard, previously, it has been declared that D1R and D2R within the nucleus accumbens (NAc) (Faramarzi et al ., 2016, 2021) and hippocampal CA1 (Abdi Dezfouli et al ., 2022) modulate acute stress-induced analgesia (SIA) in persistent inflammatory pain. In continuation, a formalin test, as an algogenic substance-induced inflammatory pain, was performed, and it was indicated that DA receptors also within the hippocampal DG play the same modulatory role in SIA (Merdasi et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%